Peranan Kompetensi Guru Terhadap Pengembangan Life Skill Siswa SMP Negeri 31 Kabupaten Halmahera Barat - Kurnia, Heri; Hasim, Jainudin; Samili, Asnita Ode (Universitas Negeri Manado, 2021)
This research aims to find out the Role of Teacher Competence Towards the Development of Life Skills of State Junior High School Students 31 West Halmahera Regency, which aims to find out several things, namely; How the role of PPKn teachers in improving the quality of teaching and learning by using the student's life skills approach. This study uses survey methods by collecting their own data a number of units in the same time (time period), which is related to how conditions, characteristic processes, results of a variable, using a set of instruments that are data collection tools and used in collecting data to make it easier and systematic. The results of this study show that Teacher Competence Towards The Development of Life Skills of State Junior High School Students 31 West Halmahera Regency, Teachers are one of the various sources and learning media, so the role of teachers in learning becomes wider and more leads to student learning motivation through his role as a teacher. Teachers are expected to be able to encourage students to always learn in various activities or opportunities through various sources and media. Teachers should help every student and effectively be able to use learning opportunities from various learning sources and media effectively and efficiently. In the learning process a teacher focuses more on aspects, planning the organization of teaching materials, planning the management of teaching and learning activities, planning the management of classes, planning the use of media and teaching resources, and planning assessment of student achievement for the benefit of teaching. Teachers must be able to make decisions on the basis of proper assessment, whether teaching and learning activities are sufficient, whether the methods are changed, whether past activities need to be repeated, while students have not been able to achieve learning goals.